Synthesis, characterization, photophysical and photochemical properties of zinc and indium phthalocyanines bearing a vanillylacetone moiety known as an anticarcinogenic agent - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The synthesis of novel peripherally/non-peripherally tetra and octa vanillylacetone-substituted zinc and indium phthalocyanines was performed by cyclotetramerization of 4-[2-methoxy-4-(3-oxobutyl)phenoxy]phthalonitrile (1)/3[2-methoxy-4-(3-oxobutyl)phenoxy]phthalonitrile (2) and 4,5-bis[2-methoxy-4-(3-oxobutyl)phenoxy]phthalonitrile (3). The novel chromogenic compounds were characterized by elemental analysis, H-1 NMR, mass spectra, FT-IR and UV-Vis spectral data. The effects of the zingerone units on the zinc and indium phthalocyanine complexes (4-9) were also investigated. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Zingerone; Vanillylacetone; Phthalocyanine; Fluorescence quenching; Singlet oxygen; PHOTODYNAMIC THERAPY; METAL-FREE; PHOTOSENSITIZERS; ZINGERONE; SENSOR; PORPHYRIN; COMPLEX; SYSTEM